Born to serve, built to last the Pernama story: secret's of Malaysia's home-grown retain chain - Abdul Wahab Khalid; Abdul Wahab Khalid (Perwira Niaga Malaysia (PERNAMA), 2015)
The inside story on how a Malaysian company led by Malaysians faced challenges head-on to become successful. PERNAMA has achieved much since it took over the armed-forces-based retail outlets from NAAFI, the well-established and hugely loved British establishment, in 1983. This book chronicles PERNAMA's journey and transformation over the years.